Prevalence of child maltreatment in the Netherlands: An update and cross-time comparison. (May 2020) - van Berkel, Sheila R.; Prevoo, Mariëlle J.L.; Linting, Mariëlle; Pannebakker, Fieke D.; Alink, Lenneke R.A.
Abstract: Background: The third Netherlands' Prevalence study of Maltreatment of children and youth (NPM-2017) continues the tradition of periodically mapping the national prevalence of child maltreatment. Objective: The NPM-2017 provides an update of the current prevalence rates of child maltreatment and of changes in its prevalence over the last 12 years. In addition, risk factors for child maltreatment and its co-occurrence with domestic violence were investigated. Participants and Setting: Prevalence data were based on cases reported to 'Safe at Home' organizations (former CPS agencies) and observations of professionals working with children (sentinels). Methods: Sentinels ( N = 785) filled out a form for each case of suspected child maltreatment that they observed within their professional sample during a three-month period. Results: An overall prevalence estimate of child maltreatment in the Netherlands in 2017 of 26–37 per 1000 children was computed. The most important risk factors for child maltreatment were low parental education ( RR= 4.95), parental unemployment ( RR = 3.64), immigrant status ( RR = 3.61), and single parenthood ( RR = 2.29). Neither prevalence rates nor risk factors changed significantly between 2005, 2010, and 2017. Finally, in 46 % of the reported families child maltreatment occurred in a context of domestic violence. Conclusions: The prevalence of co-occurring domestic violence may indicate that family violence observed within one dyad could be a marker for dysfunctional functioning of the family system. Child maltreatment remains a considerable problem in the Netherlands with a stable prevalence over the last 12 years and stability in characteristics that make families vulnerable for child maltreatment.